#TITLE_ALTERNATIVE# - MAULIDA (NIM : 15110022) ; Pembimbing I : Dr. Irwan Meilano,S.T, M.Sc ; Pembimbing II : Dr. Ir, PUTRA
Aceh earthquake on April 11th 2012 was earthquake caused by strike-slip mechanism with magnitude 8.6 Mw. The epicenter was in offshore of the west coast of northen Sumatra. The earthquake caused displacement especially for reference frames which located in the west coast of Sumatra. The value of displacement necessary to be estimated as parameter for deformation model. Besides, the postseismic effect also affected the velocity of several GPS stations which was near to the epicenter of the earthquake. The Estimation of the displacement and postseismic effect can be applied using GPS observation data. The GPS provides the information about the earthquake cycles as time series. The processing using GAMIT/GLOBK showed that there were displacement about 14 cm to the northeast because of the earthquake for GPS stations in west coast of northen Sumatra. Subsidence was also founded at the same place for 3 cm. The earthquake also caused changes for the velocity of GPS station in west coast of northen Sumatra about 4 cm/year. The effect of the earthquake was worldwide and affected the other GPS Stations around Hindia oceanic.